Scattering phase functions on the base of dynamic interaction potential - Dzhumagulova, K.N.; Shalenov, E.O.; Ramazanov, T.S.; Gabdullina, G.L. (Recent Contributions to Physics, 2014)
The phase shifts of electron-electron scattering in a dense semiclassical plasma on the base dynamic potential. Found that taking into account the dynamic charge screening at large distances in interaction of charged particles conducts to increase of phase shifts compared to the case with static shielding. Shows the decrease in the phase shifts at increase as the orbital moment, and with increasing energy of the incident particle. The problem was solved with the help of quantum-mechanical theory using equation Calogero.